Pengaruh Likuiditas, Cash Flow Dan Pertumbuhan Penjualan Terhadap Profitabilitas Pada Perusahaan Pertanian - Stevie Marthin Jordan Timothy Gultom; Fiska Sriwahyuni; Cindy Laura; Ike Rukmana Sari (STIE PGRI Dewantara Jombang, 2020)
This study aims to determine whether liquidity, cash flow and sales growth affect profitability. This study uses a quantitative approach, causal and deductive relationsh ips. The population of this research is 20 agricultural companies. To get the sample used purposive sampling technique so that the number of samples that meet the criteria of 8 companies with a period of 6 years. Data analysis methods used are multiple linear regression analysis, classic assumption test and hypothesis test. The results showed that liquidity, cash flow and sales growth had a significant effect on profitability of agricultural companies listed on the Indonesia Stock Exchange in the 2013-2018 period, but partially liquidity had a positive effect on profitability, cash flow and sales growth did not affect profitability. Based on the coefficient of determination test, it can be seen the influence of the studied variables is 20.5%, the rest is influenced by other variables not examined, that is, 79.5%.